Exploring the in vitro Anti-Inflammatory, Antioxidant, and Neuroprotective Potentials of Corchorus olitorius (L) leaves: Insights from ADME and in silico studies - Jayasingh Chellammal, Hanish Singh (Asian Journal of Pharmaceutics (AJP), 2025)
Purpose: Alzheimer’s is a progressive, irreversible, and devastating neurodegenerative disease, clinically characterized by the impairment of cognitive skills. This study investigates the pharmacological potentials of Corchorus olitorius, focusing on its anti-inflammatory, antioxidant, and neuroprotective activities through in silico and in vitro analyses. Materials and Methods: The dried leaves of C. olitorius were subjected to sequential solvent extraction followed by qualitative phytochemical analyses and gas chromatography-mass spectrometry (GC-MS) of aqueous extract. Protein denaturation, Cyclooxygenase (COX-II) inhibition, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays were used to evaluate in vitro anti-inflammatory and antioxidant potentials. Cytotoxicity, neuroprotective, and acetylcholinesterase (AChE) activities were assessed using L929 and SK-N-SH cell line, respectively. Absorption, distribution, metabolism, and excretion (ADME) and in silico studies including molecular docking against targeted proteins were performed. Results: Sterols, terpenoids, flavonoids, and phenols were found in the aqueous fraction. GC-MS analysis depicted the presence of various compounds. The dose-dependent inhibition of protein denaturation, COX-II, and cytotoxicity on normal L929 cell lines was observed. DPPH assay displayed significant antioxidant potential. Notable neuroprotective effect was found against trimethyltin chloride-induced neurotoxicity in SK-N-SH cell lines. The decreased expression of AChE activity further validates the neuroprotective potential. The ADME study predicted better gastrointestinal (GI) absorption, adherence to Lipinski rule, and drug likeness properties. The docking studies revealed favorable binding interactions with proteins of bovine serum albumin, COX-II protein, gamma-aminobutyric acid (GABA)-A receptor, and alpha-synuclein. Conclusion: Overall, the findings suggest that phytochemicals from C. olitorius leaves hold a significant potential to manage neurodegenerative diseases. Further research is warranted to validate these in silico findings through in vivo experimental studies